Aplicación del principio de mínima intervención en el delito de tala ilegal por la fema – Iquitos, del 2018-2022 - Fuertes Dávila, Manuel Alejandro (2025)
The research titled "Application of the Principle of Minimal Intervention in the Illegal Logging Offense by FEMA - Iquitos from 2018 to 2022" focuses on analyzing the application of the minimal intervention principle in cases of illegal logging in the Loreto region. The study examines the criteria used by the Specialized Environmental Prosecutor's Office (FEMA) to file illegal logging cases in the preliminary investigation stage. The methodological approach is descriptive, and exploratory. Data were collected through interviews with key legal actors and documentary analysis of prosecutorial records related to environmental crimes. The sample includes interviews with Public Ministry attorneys, forestry engineers, and other relevant professionals The results suggest that the application of the minimal intervention principle has helped reduce the prosecutorial workload by focusing on more serious cases. However, it has also faced criticism for archiving cases of minor damage to forest resources without effective penalties. Recommendations include more just and effective sanctions, along with restorative measures for minor environmental damages.